Biodegradable Si3N4 bioceramic sintered with Sr, Mg and Si for spinal fusion: Surface characterization and biological evaluation. (September 2018) - Fu, Le; Xiong, Yi; Carlsson, Gunnar; Palmer, Michael; Örn, Stefan; Zhu, Wei; Weng, Xisheng; Engqvist, Håkan; Xia, Wei
Graphical abstract: Highlights: New Si3 N4 bioceramics display high bioactivity and less in vitro bacterial affinity. Ionic dissolution products containing Sr, Mg and Si ions enhance proliferation and differentiation of MC3T3-E1 preosteoblasts. Ionic dissolution products are not toxic to the development of zebrafish embryos. Abstract: Silicon nitride (Si3 N4 ) is an industrial ceramic used in spinal fusion and maxillofacial reconstruction because of its excellent mechanical properties and good biocompatibility. This study compares the surface properties, apatite formation ability, bacterial infection, cell-biomaterial interactions, and in vivo toxicity (zebrafish) of newly developed Si3 N4 bioceramics (sintered with bioactive sintering additives SrO, MgO and SiO2 ) with two standard biomaterials; titanium (Ti) and traditional Si3 N4 bioceramics (sintered with standard sintering additives Al2 O3 and Y2 O3 ). In general, Si3 N4 bioceramics (both the newly developed and the traditional) displayed less in vitro bacterial affinity than Ti, which may arise from differences in the surface properties between these two types of material. The newly developed Si3 N4 bioceramics developed lower biofilm coverage and thinner biofilm, compared to traditional Si3 N4 bioceramics. The effects of ionic dissolution products (leach) on proliferation and differentiation of MC3T3-E1 cell were also investigated. Ionic dissolution products containing moderate amount of Sr, Mg and Si ions (approximately 4.72 mg/L, 3.26 mg/L and 3.67 mg/L, respectively) stimulated osteoblast proliferation during the first 2 days in culture. Interestingly, ionic dissolution products from the traditional Si3 N4 bioceramics that contained small amount of Si and Y ions achieved the greatest stimulatory effect for alkaline phosphatase activity after 7 days culture. The toxicity of ionic dissolution products was investigated in a putative developmental biology model: zebrafish ( Danio rerio ). No toxicity, or developmental abnormalities, was observed in zebrafish embryos exposed to ionic dissolution products, for up to 144 h post fertilization. These newly developed Si3 N4 bioceramics with bioactive sintering additives show great potential as orthopedic implants, for applications such as spinal fusion cages. Future work will focus on evaluation of the newly developed Si3 N4 bioceramics using a large animal model.